Pengaruh Kepemimpinan, Kepuasan Kerja, dan Budaya Organisasi terhadap Kinerja Pegawai di Dinas Penanaman Modal dan Pelayanan Perijinan Terpadu Satu Pintu Kabupaten Tapanuli Tengah - Primadonna Hutagalung (LITERATUS, 2021)
The success or failure of an organization in carrying out its duties and functions is closely related to organizational actors. This study aims to analyze the influence of leadership, job satisfaction and organizational culture on performance, either partially or collectively. Human resources (HR) who perform well will make it easier for the organization to achieve its vision, mission and goals. Low budget absorption can be used as a reference for assessing the low achievement of organizational performance. A person's performance can be optimal, if it supports by good leadership conditions, job satisfaction in carrying out tasks and a good organizational culture. However, if the existing conditions are not good, it can cause low employee performance. The type of research used is quantitative research with a descriptive approach and it uses multiple linear regression analysis techniques. The population chosen is the One Stop Investment Service and Licensing Service with a saturated sample size of 40 respondents. The results of this study indicate that leadership, job satisfaction and organizational culture together have a significant and positive effect on performance. Partially, leadership has a significant and positive effect on performance, job satisfaction has a significant and positive effect on performance, and organizational culture has a significant and positive effect on performance.